Kajian Yuridis Terhadap Kewenangan Pemerintah Kabupaten Jember dalam Mengawasi Pelaku Usaha Jasa Penyiaran Berlangganan - Ikrimah, Syarifatul; Fitri, Icha Chayaning (Indonesian Journal of Law and Justice, 2023)
The authority of the Jember district government in supervising subscription broadcasting service businesses. The problem in this research is what authority the Jember district government has in supervising subscription broadcasting service business actors and what the government's efforts are to deal with irresponsible subscription broadcasting service business actors. The research used is normative legal research. The data used is secondary data sourced from primary and secondary legal materials. Data analysis in this research is qualitative analysis. From the research results, it can be concluded that the authority of the Jember district government in supervising subscription broadcasting service businesses aims to ensure that the services received by the public are in accordance with predetermined standards and in accordance with applicable regulations. In this case, the government has the authority to supervise business actors in subscription broadcasting services, such as implementing regulations and rules, providing certification, monitoring and evaluation, and implementing sanctions. And in overcoming the problem of irresponsible subscription broadcasting service providers, such as installing cables on PLN electricity poles without permission, the government can do the following things: Law enforcement, coordination with PLN, outreach, imposing sanctions.